An empirical study : The relationship between personality traits and job performance / Muhammad Shahril Che Saad - Che Saad, Muhammad Shahril (Faculty of Business & Management, 2017)
This study consists of the personality traits and job performance at Faculty of Social Science and Humanity (FSSK), UKM, Bangi. The human personality can influence the way of their job performance in the organization. For this study, the main purpose is to identify whether the relationship exist between job performance and several personality traits. There are four personality traits that use to conduct the study and it is Conscientiousness, Agreeableness, Neuroticism, and Openness to experience. Random sampling method that used in collecting the respondents in the Faculty of Social Science and Humanity (FSSK). UKM, Bangi. The questionnaire was distributed to 30 people of the employees in the FSSK, UKM. An exploratory factor analysis was undertaken and Cronbach Alpha coefficients calculated to assess the reliability of the study. Other than that, the Pearson Correlation analysis was used to identify the relationship with the independent variable which is the personality traits and dependent variable, the job performance. The result of this finding shows that the individual has a high personality trait in conscientiousness with job performance to perform better in the Faculty of Social Science and Humanity (FSSK), UKM, Bangi.